2017
DOI: 10.1038/srep44322
|View full text |Cite
|
Sign up to set email alerts
|

Neurovascular microcirculatory vasodilation mediated by C-fibers and Transient receptor potential vanilloid-type-1 channels (TRPV 1) is impaired in type 1 diabetes

Abstract: Microvascular dysfunction may have an early onset in type 1 diabetes (T1D) and can precede major complications. Our objectives were to assess the endothelial-dependent (acetylcholine, ACh; and post-occlusive hyperemia, PORH), non-endothelial-dependent (sodium nitroprusside, SNP) and neurovascular-dependent (local heating, LH and current induced vasodilation, CIV) microcirculatory vasodilation in T1D patients compared with matched control subjects using a laser speckle contrast imager. Seventeen T1D patients - … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 54 publications
(102 reference statements)
1
26
0
1
Order By: Relevance
“…These studies suggest that sensory nerves may play a more important role in regulating cutaneous vasomotor activity than expected. Recent studies in humans also suggest that C-afferents play a role in mediating neurogenic vasodilation that is impaired in diabetes patients and in aged human skin [27][28][29]. In the present study we found, by using nerve deafferentation and C-afferentspecific stimulation models, that C-fiber afferents are predominantly responsible for neurogenic vasodilatation following traumatic nerve injury in the glabrous skin.…”
Section: Discussionsupporting
confidence: 65%
“…These studies suggest that sensory nerves may play a more important role in regulating cutaneous vasomotor activity than expected. Recent studies in humans also suggest that C-afferents play a role in mediating neurogenic vasodilation that is impaired in diabetes patients and in aged human skin [27][28][29]. In the present study we found, by using nerve deafferentation and C-afferentspecific stimulation models, that C-fiber afferents are predominantly responsible for neurogenic vasodilatation following traumatic nerve injury in the glabrous skin.…”
Section: Discussionsupporting
confidence: 65%
“…19 Several of these studies have shown that activation of transient receptor potential vanilloid type 1 (TRPV1) in neurons plays an important role in peripheral neuralgia caused by diabetes. [20][21][22] A research showed that in the streptozotocin-induced diabetic rat model, lncRNA BC168687 siRNA increased the thermal withdrawal latency (TWL) and mechanical withdrawal threshold (MWT) of diabetic rats and alleviated DPN by regulating transient receptor potential vanilloid type 1 (TRPV1) and cytokines (TNF-α and IL-1β). 23 The production of TNF-α and IL-1β and other inflammatory factors is closely related to the activation of ERK (extracellular regulated protein kinases) and p38 pathways.…”
Section: Lncrna Bc168687mentioning
confidence: 99%
“…Als nozizeptive Sensoren der C-und Aδ-Fasern gelten unter anderem die Transient Receptor Potenzial (TRP) Kanäle, zu deren aktivierenden und sensitivierenden Faktoren Hitze oder Kälte, Protonen, reaktive Sauerstoffspezies, Stickstoffmonoxid sowie intrazelluläre Modulationswege zählen [38]. TRPV1-Kanäle aus C-Fasern sind gleichzeitig auch verantwortlich für die Peak-Vasodilatation nach Ischämie oder Stauung [39].…”
Section: Nervenschädigung Und Neurogene Inflammation -Die Brücke Zum unclassified